Serum Levels of Semaphorin 4C in Breast Cancer – Assessment of Prognostic Value and Potential for Monitoring Surgical Treatment Response - Popov Ts.; Maslyankov S.; Arabadzhiev A.; Sokolov M.; Kandilarova S. (Acta Medica Bulgarica)
Introduction. The global burden of breast cancer (BC) has encouraged ceaseless research in exploring novel biomarkers, aiming to optimize BC management and prognosis.